Role of Dielectric Constant on Ion Transport: Reformulated Arrhenius Equation - Shujahadeen B. Aziz (Advances in Materials Science and Engineering)
Solid and nanocomposite polymer electrolytes based on chitosan have been prepared by solution cast technique. The XRD results reveal the occurrence of complexation between chitosan (CS) and the LiTf salt. The deconvolution of the diffractogram of nanocomposite solid polymer electrolytes demonstrates the increase of amorphous domain with increasing alumina content up to 4 wt.%. Further incorporation of alumina nanoparticles (6 to 10 wt.% Al2O3) results in crystallinity increase (large crystallite size). The morphological (SEM and EDX) analysis well supported the XRD results. Similar trends of DC conductivity and dielectric constant with Al2O3 concentration were explained. The TEM images were used to explain the phenomena of space charge and blocking effects. The reformulated Arrhenius equation (σ(ε′,T)=σoexp(-Ea/KBε′T)) was proposed from the smooth exponential behavior of DC conductivity versus dielectric constant at different temperatures. The more linear behavior of DC conductivity versus 1000/(ɛ′×T) reveals the crucial role of dielectric constant in Arrhenius equation. The drawbacks of Arrhenius equation can be understood from the less linear behavior of DC conductivity versus 1000/T. The relaxation processes have been interpreted in terms of Argand plots.